Management of median and paramedian craniofacial clefts. Issue 4 (April 2019) - Rüegg, Eva Meia; Bartoli, Andrea; Rilliet, Bénédict; Scolozzi, Paolo; Montandon, Denys; Pittet-Cuénod, Brigitte
Summary: Background: Median and paramedian craniofacial clefts are associated with hypertelorism, anterior encephalocele, positional abnormalities of the maxilla, and nasal deformity. Cleft lip and palate, eyelid coloboma, and widow's peak are frequently present. Methods: The authors collected data from 30 patients (mean age, 5.8 years; range, 4 months to 18 years) operated between 1986 and 2017 with median or paramedian craniofacial clefts of differing degrees of severity. Malformations of the different anatomic units and their surgical treatment were assessed, as well as complication rates. Results: All patients presented nasal malformations and either telecanthus (n = 16) or hypertelorism (n = 14). Most patients (n = 23) had anterior encephalocele. All patients underwent nasal corrections, and most of them had medial canthopexy (n = 24). Excision of encephalocele was associated with fronto-orbital remodeling. Medialization of the orbits was performed in 11 patients, mainly by box shift (n = 9). Patients from outside Switzerland (n = 23) were operated at an older age than those in the native patient group. Because of staged reconstruction, 13 patients had more than one operation. Surgical complications included three infections and one expander exposition. One patient had bone resorption of a frontal bone flap. Nasal correction needed more than one procedure in 5 patients, and medial canthopexy had to be repeated in 7 patients. Esthetic results were satisfactory, permitting social integration. Conclusion: Median and paramedian craniofacial clefts need adapted and carefully planned corrections respecting the growth of anatomic units. The quality of the medial canthal and nasal reconstruction is to a large extent responsible for the overall result.